Of exploited reefs and fishers – A holistic view on participatory coastal and marine management in an Indonesian archipelago. (November 2015) - Glaser, Marion; Breckwoldt, Annette; Deswandi, Rio; Radjawali, Irendra; Baitoningsih, Wasistini; Ferse, Sebastian C.A.
Abstract: This paper arises from a four-year Indonesian-German research cooperation on the governance and management of Indonesian coastal and marine ecosystems. Project objectives were to investigate coastal and marine social-ecological dynamics and feedbacks and to analyse socio-political and institutional structures and processes in order to support adaptive coastal governance. Participating researchers worked in the Spermonde Archipelago, off South Sulawesi, Indonesia, between 2007 and 2010. Methods included ship-based research excursions, several classical surveys, anthropological participant observation, and participatory research methods applied by an interdisciplinary social-natural science team. This paper summarises our findings and draws policy conclusions. First, we discuss Marine Protected Areas and participation focussing on local "rules-in-use". In addition, reef exploitation and local livelihoods, in particular fisheries and mariculture, and the existing social networks and hierarchies in fisheries are explored to understand social vulnerability, resilience and marine resource governance in the context of the Spermonde Archipelago. An outline of major policy recommendations concludes this article. Highlights: Marine resource use and management in an Indonesian Archipelago were investigated. Island residents depend strongly on their heavily exploited marine environment. Equal, broad and meaningful local participation in management efforts is needed. Conservation-related benefits need to be balanced to reduce social vulnerability.